ANALYSIS OF FINANCIAL PERFORMANCE OF BANK MUAMALAT INDONESIA BASED ON ISLAMICITY PERFORMANCE INDEX PERIOD 2013 – 2020 - Rini Dwiastutiningsih; Dila Apriani (Institut Agama Islam Sultan Muhammaad Syafiuddin Sambas, 2022)
The development of Islamic banking in Indonesia is very important, especially since Indonesia has a majority Muslim population. Therefore, the performance of Islamic banking in Indonesia is very important to gain the trust of customers who want to deposit funds or distribute funds. Basically, Islamic banking carries out its activities using sharia principles to be free from usury. The purpose of this study was to determine the performance of Bank Muamalat Indonesia based on the Islamicity Performance Index (IPI) method in the period 2013-2020. This study uses quantitative methods with the type of research is descriptive research through secondary data. The results of the analysis of the financial performance of Bank Muamalat Indonesia based on the Islamicity Performance Index (IPI) method on the financial performance of Bank Muamalat Indonesia are good. This can be seen in the indicators of the Islamicity Performance Index (IPI) of Bank Muamalat Indonesia's financial performance as follows: Profit Sharing Ratio (PSR) from the results of the analysis is in good predicate, Zakat Performance Ratio (ZPR) results in poor predicate, Equitable Distribution Ratio (EDR) which includes Qardh and Donation in good predicate, Employee Expense in good predicate, while for Net Profit in poor predicate, Islamic Investment vs Non-Islamic Investment Ratio in very good predicate, and Islamic Income vs Non-Islamic Income in very good predicate.